2008
DOI: 10.1002/app.25127
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a series of SPEEK/TiO2 hybrid membranes for direct methanol fuel cell

Abstract: Through sol‐gel reactions, a series of sulfonated poly(ether ether ketone) (SPEEK)/TiO2 hybrid membranes with various contents of nano‐sized TiO2 particles were prepared and characterized. It was found that with the increasing of the TiO2 contents in the hybrid membranes, the water uptake and water retention increased. Meanwhile, the introduction of inorganic particles reduced the methanol permeability. The proton conductivity was enhanced by introduction of hydrophilic inorganic particles into the SPEEK membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Nafion117 was pre-treated by boiling in distilled water followed by 3% H 2 O 2 and 0.5M H 2 SO 4 at 80 °C for one hour each. The pre-treated membrane is stored in distilled water (Dou et al 2008;Xin et al 2014).…”
Section: Membrane Preparationmentioning
confidence: 99%
“…Nafion117 was pre-treated by boiling in distilled water followed by 3% H 2 O 2 and 0.5M H 2 SO 4 at 80 °C for one hour each. The pre-treated membrane is stored in distilled water (Dou et al 2008;Xin et al 2014).…”
Section: Membrane Preparationmentioning
confidence: 99%
“…[22][23][24] Therefore, many research efforts to prepare more stable and mechanically strong membranes have also been undertaken through several methods, such as the addition of hydrophilic inorganic materials, blending with polymeric materials, and the formation of a crosslinking network. [25][26][27][28][29] Crosslinking is thought to be a simple and powerful method to improve the low mechanical properties and dimensional stability. Recently, Mao et al 30 reported that crosslinked SPEEK membranes with aromatic or aliphatic amines have improved mechanical properties and dimensional stability.…”
Section: Introductionmentioning
confidence: 99%
“…However, the SPEEK membrane with a high degree of sulfonation is well known to be hampered by particularly low mechanical properties and dimensional stability owing to the excessive water swelling . Therefore, many research efforts to prepare more stable and mechanically strong membranes have also been undertaken through several methods, such as the addition of hydrophilic inorganic materials, blending with polymeric materials, and the formation of a crosslinking network …”
Section: Introductionmentioning
confidence: 99%
“…However, at a low degree of sulfonation, the hydrophilicity of the polymer is too weak to attain adequate proton conductivity values. Therefore, numerous approaches, such as acid-base interactions, [9][10][11][12] organic-inorganic hybrids [13][14][15][16][17][18][19] and crosslinking, [20][21][22] have been taken to improve the dimensional stability, water retention capacity and proton conductivity of membrane materials without sacrificing methanol permeation. Generally speaking, the interactions between acid and base polymers in hybrid membranes, such as ionic cross-linking (electrostatic forces) and hydrogen-bonding bridges, contribute markedly to control the swelling and methanol permeation of hybrid membranes.…”
Section: Introductionmentioning
confidence: 99%